Efek Toksisitas Subakut Ekstrak Etanolik Daun Jambu Biji (Psidium guajava) pada Lambung Tikus Wistar - Esti Dyah Utami; Hanif Nasiatul Baroroh; Nuryanti Nuryanti (Fakultas Farmasi Universitas Pancasila, 2018)
Psidium guajava leaves have been proven be antiallergic. From the results of previous research, the ethanol extract of leaves is included in the class materials